A Current Approach in Animal Breeding: CRISPR/Cas9 Genome Modification System - Fatih Bilgi; Zeynep Demirtaş; Levent Mercan (Turkish Journal of Agriculture: Food Science and Technology)
Genome modifications include potential about providing significant advantages on increasing yield performance and developing resistance to diseases. Gene editing methods that provides silencing or expressing of a gene which is an individual already has, have important potential for improving genetic structure without environmental effects. In recent times, new gene editing systems were developed. These are ZFNs (Zinc Finger Nucleases), TALENs (Transcription Activator-like Effector Nucleases) and CRISPR/Cas nuclease systems. CRISPR/Cas system is a microbial immune system that uses RNA guided nucleases for destroying genetic materials and its potential usage like a simple and efficient gene editing mechanism in animals is being evaluated recently. In this review, we summarized CRISPR/Cas9 system and its usability in animal breeding